PERFORMANCE EVALUATION ON THE DESIGNED V-SHAPED MONOHULL SHIP MODELS - Prabowo, Aditya Rio; Febrianto, Rizky Adhi; Tuswan, Tuswan; Tjahjana, Dominicus Danardono Dwi Prija (Journal of Applied Engineering Science, 2022)
A typical ship must operate in extreme conditions in the open coastal zone. Due to the severe operation at sea, comparative research on the design of the hull shape for optimization purposes will be important, specifically in the resistance and movement aspect. In this regard, an investigation was carried out by varying the total of four V-shaped monohull models from the high-built design as the main subject to compare several hull shape designs at the same displacement to obtain better performance at stability, resistance, and seakeeping criteria. Savitsky formula is used to calculate the hull resistance, and the stability analysis is calculated analytically by comparing the relationship between righting arm and heel angle. Moreover, ship motion is investigated by examining heave and roll response amplitude operator (RAO) and Motion Sickness Incident (MSI) index due to wave height 0.1 m. The most significant feature in this study is resistance since, with limited power, a minimum resistance value is necessary for best outcomes. It can be found that Model I is a superior model in terms of resistance, stability, and seakeeping performance to other models. However, Model III is not recommended since it has high resistance and bad stability and motion performance. From these results, it can be summarized that Model I is selected as the best hull form model.